Recyclability and reusability of the solvents - Quah H.B.; Liu X.; Chia S.R.; Nomanbhay S.; Show P.L. (Elsevier, 2024)
Solvents are widely used in the chemical industries, often for the separation or purification process or the production of chemicals. However, the usage of solvents has also been greatly reduced due to the environmental concerns as well as the aim in achieving a greener chemistry. Thus, it is extremely crucial for us to not underestimate the importance of environmental technologies in solvent recycling to attain a sustainable environment. Since most of the products obtained from biotechnological processes are generally in a dilute state, having a large amount of contaminated substances that share the same chemical and physical characteristics. As a result of that, most of the solvents are being incinerated or being disposed to the environment. In the contrary, some reported that the cost of spent solvent treatment may be high depending on the standard of the solvents. Therefore in this chapter, the mandatory requirements and standards on recovering spent solvents will be covered as well as the feasibility of the spent solvent treatment process. Major factors such as the size of the bioparticles and impurities, desired concentration, and process throughput may have an impact on the selection of the separation process in recycling spent solvents. By developing an economical and efficient separation method in recovering spent solvents, the selection of separation methods will be crucial in order to achieve a successful commercialized bioseparation process. Hence, various separation technologies will also be covered in this chapter by emphasizing the selection of separation methods to be applied in large-scaled implementations. 2023 Elsevier Inc. All rights reserved.